Educational Data Mining: An Efficient Framework to Learning Theory: Utilizing Data Mining for Enhanced Learning and Evaluation in E-Learning (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Data mining implies specific examples inside huge arrangements of data, which makes a great deal of conceivable outcomes for leaders. By investigating those examples, better choices can be made so as to enhance learning and evaluation process. The exploration enthusiasm for utilizing DM (data mining) in e-learning is always expanding.